Askin tumor: a rare tumor of the chest wall (Archives of Pediatrics of Uruguay, 2023)
Askin tumor or primitive neuroectodermal tumor is a small round cells’ neoplasia, which originates in the chest’s soft tissues probably from embryonic cells that migrate from the neural crest. They are very aggressive tumors that metastasize and disseminate quickly.Clinically, patients show a soft tissue mass in the chest that may or may not be accompanied by pain. Other manifestations include dyspnea, cough, weight loss, Horner syndrome and regional lymphadenopathy. Chest radiographies show a usually large extrapulmonary heterogeneous mass, which can completely opacify the hemithorax.The prognosis is poor; however, the combined use of chemotherapy, surgery and radiation has improved results dramatically.
Keywords: Askin’s tumor; Thoracic wall; Radiology